2022
DOI: 10.1128/iai.00099-22
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus lugdunensis Uses the Agr Regulatory System to Resist Killing by Host Innate Immune Effectors

Abstract: Coagulase-negative staphylococci (CoNS) are frequently commensal bacteria that rarely cause disease in mammals. Staphylococcus lugdunensis is an exceptional CoNS that causes disease in humans similar to virulent Staphylococcus aureus , but the factors that enhance the virulence of this bacterium remain ill defined. Here, we used random transposon insertion mutagenesis to identify the agr quorum sensing system as a regulator of hemolysins i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…There is limited information concerning the replication/survival of CoNS in macrophages. The facultative pathogens S. lugdunensis (Chin et al., 2022) and S. epidermidis (Oliveira et al., 2022; Spiliopoulou et al., 2012) were shown to be killed within macrophages. Of note, for S. epidermidis , we could not link biofilm formation to bacterial survival.…”
Section: Discussionmentioning
confidence: 99%
“…There is limited information concerning the replication/survival of CoNS in macrophages. The facultative pathogens S. lugdunensis (Chin et al., 2022) and S. epidermidis (Oliveira et al., 2022; Spiliopoulou et al., 2012) were shown to be killed within macrophages. Of note, for S. epidermidis , we could not link biofilm formation to bacterial survival.…”
Section: Discussionmentioning
confidence: 99%
“…There is limited information concerning replication/survival of CoNS in macrophages. The facultative pathogen S.lugdunensis (Chin et al, 2022) and S. epidermidis (Oliveira et al, 2022;Spiliopoulou et al , 2012) were shown to be killed within macrophages. Of note, for S. epidermidis we could not link biofilm formation to bacterial survival.…”
Section: Discussionmentioning
confidence: 99%
“…S. lugdunensis shares genomic features with S. aureus ( 29 ), and our results showed that the agr system might play a role in lugdunin production. To date, the agr locus in S. lugdunensis has been shown to play a role in biofilm formation and resistance to host immune killing; however, its role in lugdunin production has not been investigated ( 17 , 18 ). Therefore, our study provides a potential role of agr in the regulation and production of S. lugdunensis lugdunin.…”
Section: Discussionmentioning
confidence: 99%
“…Most virulence factors in S. aureus are closely regulated by the agr locus, which encodes a two-component signaling pathway that can be divided into four major agr groups: types I–IV ( 16 ). The agr locus in S. lugdunensis was recently shown to play a role in biofilm formation and resistance to host immune killing ( 17 , 18 ). Hence, despite well-reported evidence regarding the chemical structure and biosynthetic gene clusters of lugdunin, the epidemiology of lugdunin-producing strains and the association of lugdunin production with STs, SCC mec , and agr genotypes are still unknown.…”
Section: Introductionmentioning
confidence: 99%